COMMON EFFLUENT TREATMENT PLANT - MR. VENUGOPAL T. LAKAPATI; MR. VENUGOPAL D. GALPALLI; MR. RAHUL S. ADAM (International Journal of Innovations in Engineering Research and Technology, 2021)
The increasing demand for water in combination with frequent drought periods, even in areas traditionally rich in water resources, puts at risk the sustainability of current living standards. In industrialized countries, widespread shortage of water is caused due to contamination of ground and surface water by industrial effluents, and agricultural chemicals. Global trends such as urbanization and migration have increased the demand for water, food and energy. Development of human societies is heavily dependent upon availability of water with suitable quality and in adequate quantities, for a variety of uses ranging from domestic to industrial supplies and Rapid industrialization is adversely impacting the environment globally. Pollution by inappropriate management of industrial wastewater is one of the major environmental problems in India as well, especially with small scale industrial sector in the country. To address the pollution coming out from industries, adoption of cleaner production technologies and waste minimization initiatives are being encouraged.